Pengaruh Literasi Keuangan Syariah, Brand Equity, dan Kepercayaan Terhadap Keputusan Gen Z dalam Menggunakan Jasa Perbankan Syariah - Ismawati; Nurjannah; Isda Iskandar; Misra Windayani (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2025)
The development of Islamic banking is accompanied by increasing public awareness of Islamic finance and support from government regulations. Generation Z is known as a digital and critical generation, making it very potential in supporting the development of Islamic banking. This study aims to analyze the influence of Islamic financial literacy, brand equity and trust on Generation Z's decisions in using Islamic banking services. This study is a quantitative study with associative-causal, the data analysis technique used is multiple linear regression. The results of the study indicate that Islamic financial literacy does not affect Generation Z's decisions in using Islamic banking services. Brand equity and trust have a positive effect on Generation Z's decisions in using Islamic banking services. And simultaneously Islamic financial literacy, brand equity and trust have a positive and significant effect on Generation Z's decisions in using Islamic banking services. Islamic banks need to further improve brand equity and pay attention to and maintain customer trust so that customers are interested in using Islamic banking services.